The birth of Dolly and xenotransplantation 25 years on. (22nd November 2022) - Nottle, Mark B.; Hawthorne, Wayne J.; Cowan, Peter J.
Abstract: A number of reviews have been written recently celebrating the 25th anniversary of the birth of Dolly the cloned sheep and the effect this breakthrough has had on various fields of research. However, arguably the biggest impact Dolly has had is on the field of xenotransplantation, described here based on our own experience and that of others.